(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
After the promulgation of Law 9.615 / 1998, known as Pelé Law, the sports bodies have been regulated by market laws with the same duties as other private companies. In 2004, through resolution 1.005, the Federal Accounting Council(CFC) approved the NBC T 10:13 in order to establish specific criteria and assessment procedures concerning evaluation and accounting records and also concerning the structure of financial statements of professional football entities and other professional sports practices. This study aimed to verify whether the financial statements of the clubs of Santa Catarina Football Championship 2012 were presented in accordance with current accounting legislation. To this end, this research had an exploratory-documentary character, therefore the research elements were observed, analyzed and compared. To achieve the result, this study used the statements published by the clubs and the analysis model adapted from Souza (2013), with 12 items covered in the norm NBC 10:13 T , being held in six clubs that presented their statements concerning the year of 2012, which are: Avai, Criciúma, Hermann Aichinger, Figueirense, Joinville and Metropolitano. It was concluded that, while there are clubs close to conformity to the norm requirements, there are others that are behind this compliance, requiring more attention and responsibility of sports managers, especially for professionals responsible for accounting. It was also concluded that Santa Catarina clubs are within the national average in relation to the comparison made with the study of Souza (2013).